Preventive Health Behaviors of Community During Covid-19 Pandemic: A Descriptive Study - Ika Purnamasari; Anisa Ell Raharyani (Indonesian Journal of Global Health Research, 2020)
The pandemic of coronavirus disease (COVID-19) has been declared by World Health Organization on March 11, 2020. COVID-19 is a disease caused by SARS-CoV-2. Some of preventive behaviors have been recommended to minimize the risk of COVID‐19 infection in the general population, including staying-at-home orders, hand hygiene, prohibitions against mass gatherings, wearing a mask, and maintaining physical distance between persons. To describe community behaviors related to the implementation of the recommendation on covid-19 preventions. This research was a descriptive study involving 144 respondents as the community members of Wonosobo District, Indonesia. The data was analysed using descriptive analysis. The study showed that among the community involved, 95.8% of them were categorized as good, while the remaining 4.2% was categorized as enough. The category of good community behaviors was pointed out by the indication in which 77.8% of the community obeyed staying-at-home orders. As much as 56% of them still went shopping for groceries and 44.4% utilized both on-line shopping and delivery service facilities. Other good behaviors were indicated by 96.5% of the community were discipline in applying hand washing, 93.1% of them kept the distance to others and avoided gatherings as well as 68.1% of the people kept wearing masks. The behaviour of the majority of the community were categorized as good. This condition is expected to support efforts to handle the COVID-19 cases to be carried out effectively.